2009
DOI: 10.1084/jem.20082387
|View full text |Cite
|
Sign up to set email alerts
|

Activating receptors promote NK cell expansion for maintenance, IL-10 production, and CD8 T cell regulation during viral infection

Abstract: Natural killer (NK) cells have the potential to deliver both direct antimicrobial effects and regulate adaptive immune responses, but NK cell yields have been reported to vary greatly during different viral infections. Activating receptors, including the Ly49H molecule recognizing mouse cytomegalovirus (MCMV), can stimulate NK cell expansion. To define Ly49H's role in supporting NK cell proliferation and maintenance under conditions of uncontrolled viral infection, experiments were performed in Ly49h−/−, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
218
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(231 citation statements)
references
References 79 publications
11
218
1
1
Order By: Relevance
“…Several cells in the immune system, including NK cells, produce IL-10 early after MCMV infection. The early production of IL-10 promotes virus replication in the salivary glands by negatively affecting the maturation of DCs, leading to poor priming of T cells (26,27). We found that splenic Ly49H + and Ly49H -NK cells from the mice produced similar levels of IL-10 at day 2.5 post-MCMV infection (Fig.…”
Section: Ebi3 Promotes Il-10 Production By Nk Cells and Negatively Afmentioning
confidence: 63%
See 3 more Smart Citations
“…Several cells in the immune system, including NK cells, produce IL-10 early after MCMV infection. The early production of IL-10 promotes virus replication in the salivary glands by negatively affecting the maturation of DCs, leading to poor priming of T cells (26,27). We found that splenic Ly49H + and Ly49H -NK cells from the mice produced similar levels of IL-10 at day 2.5 post-MCMV infection (Fig.…”
Section: Ebi3 Promotes Il-10 Production By Nk Cells and Negatively Afmentioning
confidence: 63%
“…and in the serum at day 5 p.i. As reported previously, production of IL-10 early during MCMV infection is important for limiting DC maturation and T-cell activation to prevent harmful immune-mediated tissue damage in the host (26,27). During MCMV infection, IL-10 production by NK cells and other immune cells can suppress the maturation DCs, leading to poor priming of CD4 + T cells (26).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Des résultats similaires ont également été obtenus dans un modèle de vaccination utilisant de l'ovalbumine en présence d'un adjuvant [24]. Il a été également démontré, dans des souris déficientes pour la perforine, que les cellules NK Ly49H + peuvent directement supprimer la réponse des lymphocytes T CD8 anti-MCMV en sécrétant de l'IL-10 [25] (Figure 4B). En résumé, toutes ces études ont montré que l'activation des cellules NK a un impact sur l'immunité cellulaire T. Ces travaux suggèrent que par leur action sur (1) la charge antigénique, (2) la quantité et la fonctionnalité des cellules dendritiques conventionnelles, et (3) le niveau des cytokines inflammatoires, les cellules NK influencent positivement ou négativement l'activation des lymphocytes T. Alors que la cytotoxicité des cellules NK contribue largement aux défenses antivirales, on peut s'interroger sur l'avantage biologique qu'il y a à limiter les réponses adaptatives.…”
Section: Un Rôle Immunorégulateur Pour Les Cellules Nkunclassified